Crossmodal correspondences of tastes : an investigation with a blind tasting of lemonade - Kwang, Pearlyn Kwai Foong (2015)
Past research investigating crossmodal correspondences of tastes has found that certain tastes are consistently paired with particular speech sounds and shapes. For example, bitter chocolates are paired with angular shapes and sounds like ‘kiki’ (Ngo, Misra & Spence, 2011), while sweet juices are paired with rounder shapes and sounds like ‘bouba’ (Ngo et al., 2013). This study aimed to expand on the established crossmodal correspondences by evaluating two flavor dimensions simultaneously: sweetness and sourness in a blind tasting of lemonade. Tactile-taste associations were also investigated; specifically, if the tactile perception of an object shape (e.g. spiky or round) can implicitly bias a participant’s taste ratings. Fifty Singaporean participants blind-tasted nine sweet-sour combinations of lemonades and rated the sweetness and sourness level of the juice on a physical scale by dropping either a pointy ball or a round ball into fixed rows of cups. They then performed both sound and shape selection tasks. Results showed that: 1) Participants were more likely to give higher sourness ratings with a round ball than a pointy ball, 2) Sound [i] was paired with sourness, but sound mapping for sweetness was random and, 3) An increase in sourness was mapped onto an increase in convolutions, and an increase in sweetness to an increase in roundness. Implications of these findings in understanding the underlying mechanisms of crossmodal correspondences are discussed. In particular, findings were not entirely supportive of Ramachandran and Hubbard’s (2001) postulation that crossmodal correspondences are based on similarity of abstract features, and suggested the presence of other mechanisms like hedonic and intensity matching.